Peran Strategi Badan Wakaf Indonesia (BWI) Dalam Meningkatkan Profesionalisme Nazhir Kota Semarang - Harahap, Muhammad Budi Buchari; Darwanto, Darwanto (TAWAZUN: Journal of Sharia Economic Law, 2021)
Nazhir's problem is one of the problems in waqf practice that is often encountered in the management of waqf today. These obstacles are due to the low quality of human resources, lack of understanding of Nazhir, and lack of guidance given to Nazhir. This paper will discuss about the security of waqf in the city of Semarang, selling nazhir and implementing strategies by the Indonesian Waqf Board in order to create Nazhir professionalism. The purpose of this research is to find out the problems between waqf assets, Nazhir and the Indonesian Waqf Board and to formulate what solutions can solve them. This study uses a qualitative method with a descriptive approach, data observation, observation, and document review. The results showed that there were still many waqf assets found without complete administration so that representatives of BWI Central Java were focused on strategies to control existing waqf assets and the training received by Nazhirs in Semarang City was not sufficient to produce professional Nazirs. The mindset, understanding and work ethic of the Nazhirs are still traditional to create a productive climate of waqf which is beneficial for the economy of society.